Improving irrigation effieciency: Raingun performance in field scale vegetable production - Lacey, T. R. (Cranfield University, 2006)
In England and Wales, rising demands on water resources and competition between sectors is leading to increased pressure on field vegetable growers to irrigate more efficiently. Approximately 40,000ha of field scale vegetables are irrigated in England and Wales in a dry year. Between 60% and 90% of this area is estimated to be irrigated using hose-reels fitted with rainguns. However, despite their popularity, these systems are inherently non-uniform in water distribution, particularly in windy conditions. Improving their application uniformity has therefore been identified as one of the most practical solutions to increasing irrigation efficiency for field vegetable growers. This thesis develops an integrated approach to model the spatial and temporal impacts of irrigation non-uniformity on the yield and quality of a vegetable crop grown in the UK. The research used carrots as a representative crop because of their sensitivity to irrigation and high importance within the field vegetable sector. The impacts of a range of raingun equipment and management strategies (field orientation, lane spacing, sector angle, night versus day irrigation) have been evaluated. Two models were used to simulate raingun irrigation. TRAVGUN was first used to generate a database of wind affected wetted pattems for a typical raingun system. 'TRAVELLER' then simulated raingun movement down and across a field, applying these pattems according to ambient wind conditions and a pre-defined range of equipment and management strategies. Carrot yield response to spatially variable irrigation was simulated using the model Carrot Calculator". A spreadsheet model was also developed to quantify the impacts of irrigation non-uniformity on carrot quality. The models were calibrated and validated using data collected during 2003 and 2004 from field sites on commercial farms in East Anglia. The outputs from the research include new information, datasets and detailed maps showing the spatial and temporal pattems of irrigation application and their consequent impacts on crop yield and quality. The findings demonstrated that the raingun equipment and management strategies employed by growers can have a considerable impact on application uniformity, and hence on crop production. Of particular importance were the closely linked variables of lane spacing and sector angle. The I analyses suggested that the highest application uniformity occurred using a lane spacing of 70 m and a sector angle of 210° where wind speeds were <2 m s". At higher wind speeds, narrowing the lane spacing to 60 m and using a sector angle of 180° (or 210Â ° where the wind speed was greater than 3 m s`l) provided maximum uniformity. If the lane spacing cannot be altered from 70 m, increasing the sector angle to 240° at higher wind speeds improved uniformity. The industry recommended lane spacing of 72 m may therefore be marginally too wide, particularly under windy conditions. The research also confirms that orientating fields/travel lanes perpendicularly to the prevailing wind direction and irrigating at night when wind speeds are typically lower can help reduce application non-uniformity. These findings have helped to substantiate many of the measures being widely discussed for improving irrigation efficiency. The integrated approach has also enabled the combination of various equipment and management strategies to be more thoroughly evaluated than was previously possible. Irrigation uniformity was found to have a considerable impact on carrot crop yield and, in particular, quality. For example, in a typical dry year, simulated non-uniform irrigation resulted in a total yield loss of 4%, a marketable yield loss of 8% and a premium root yield loss of 11%. This could have resulted in an income loss of approximately .E288-585 ha" (4-8%). Importantly, and contrary to grower perceptions, this research demonstrated that a small but appreciable crop loss (up to 1%) may occur due to just a single non-uniform irrigation during critical crop growth periods. This research has provided useful insight and new information in support of developing recommendations to assist growers not only in improving their crop production but also in demonstrating efficient irrigation both for meeting grower protocol requirements and at abstraction licence renewal. I addition, the findings will help inform the regulatory authorities on the complexities and difficulties of achieving efficient irrigation. The research approach could also be readily utilised by manufacturers to assist in designing and improving raingun equipment. Although the modelling approach was developed for raingun irrigated carrots, the methodology could be readily extended to other crops and overhead irrigation systems to provide tools for growers and the crop services industry to evaluate system performance and the impacts for crop production.